For earth's sake the life and times of David Brower - de Graaf, John; KCTS Television (Oley, PA : Bullfrog Films, 1989)
A portrait of David Brower, America's leading environmentalist. He was instrumental in establishing some of America's most spectacular national parks
Copy in DVD Format
Director of photography, Tom Speer ; associate producer, Carolyn Gates
Narrator: Leila Gorbman
VHS Format
Keywords: Brower, David Ross, -- 1912-2000; Conservation of natural resources; Environmentalists